Designing Performance Management System Based on Integrated Performance Management System - Husodo, Widodo Kukuh Sujatmiko; Wibisono, Dermawan (Journal of Business and Management, 2017)
AbtractIndonesia rated shoe market is worth 29.3 trillion rupiahs, with spending on footwear family unit expands by 47% during the period 2007 to 2012 (Euromonitor International). Minen Leather is a manufacturer of leather shoes and other leather goods. But after running for five years, had several problems, as they can not increase revenue. The purpose of this study was to develop a vocational school, which is output in the form of Key Performance Indicators (KPI), in Minen Leather, to achieve that goal required an understanding of the IPMS Framework and Strategic Management process. The method used to develop the vocational school is to analyze the vision and mission, evaluate the internal and external situation, identify the Critical Success Factors (CSF), choose the variable performance based on the perspective of the framework IPMS.According to the data analysis showed that Minen Leather need to change their vision and mission should be formed to control the activities of the company. Assessment external and internal conditions revealed that Minen Leather should apply the